Représentations de l'écrit et image de soi : les obstacles à l'apprentissage. Un retour sur expérience - Anne Torunczyk (Les éditions de la Maison des sciences de l'Homme, 2013)
Based on her observations and on learners 'own words, the author, who teaches adults having various reading and/or writing difficulties, analyzes their mental representations of writing. For some of them, written language appears as series of images-words, of ideograms than need to be memorized and that are mute by definition. For others, the almighty orthography masks the phonetic nature of written language which appears as an inaccessible knowledge. All their mental representations show a total discrepancy between the spoken words, their words and the writing, considered as the school or the elite language. For some children, school does not allow their questions and thinking about writing to mature and in turn puts them in a situation of failure, with deep repercussions on their self-image all along their adult life. This failure is tightly linked to a sneaky social discrimination resulting from a compulsive, "legitimate", unique and unchanged language. This language of the school and the elite excludes people speaking popular languages, who feel humiliated and powerless. Learning implies a deep transformation of all these mental representations, but also another approach look from trainers and teachers.